HIV-1 Gag specifically restricts PI(4,5)P2 and cholesterol mobility in living cells creating a nanodomain platform for virus assembly - Favard, C; Chojnacki, J; Merida, P; Yandrapalli, N; Mak, J; Eggeling, C; Muriaux, D (American Association for the Advancement of Science, 2019)
HIV-1 Gag protein assembles at the plasma membrane of infected cells for viral particle formation. Gag targets lipids, mainly PI(4,5)P2, at the inner leaflet of this membrane. Here, we address the question whether Gag is able to trap specifically PI(4,5)P2 or other lipids during HIV-1 assembly in the host CD4+ T lymphocytes. Lipid dynamics within and away from HIV-1 assembly sites were determined using super-resolution microscopy coupled with scanning fluorescence correlation spectroscopy in living cells. Analysis of HIV-1-infected cells revealed that, upon assembly, HIV-1 is able to specifically trap PI(4,5)P2 and cholesterol, but not phosphatidylethanolamine or sphingomyelin. Furthermore, our data showed that Gag is the main driving force to restrict the mobility of PI(4,5)P2 and cholesterol at the cell plasma membrane. This is the first direct evidence highlighting that HIV-1 creates its own specific lipid environment by selectively recruiting PI(4,5)P2 and cholesterol as a membrane nanoplatform for virus assembly.